2021
DOI: 10.1186/s12955-021-01825-6
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and physical activity in children with inherited cardiac arrhythmia or inherited cardiomyopathy: the prospective multicentre controlled QUALIMYORYTHM study rationale, design and methods

Abstract: Background Advances in paediatric cardiology have improved the prognosis of children with inherited cardiac disorders. However, health-related quality of life (QoL) and physical activity have been scarcely analysed in children with inherited cardiac arrhythmia or inherited cardiomyopathy. Moreover, current guidelines on the eligibility of young athletes with inherited cardiac disorders for sports participation mainly rely on expert opinions and remain controversial. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
1
4
0
1
Order By: Relevance
“…Psychometric properties showed reliability, validity, and responsiveness to clinical change over time, including the French version of the PedsQL. 45 , 46 In previous studies using various HRQoL instruments, 37 , 43 , 47 , 48 our group also found a good sensitivity of the PedsQL generic questionnaire in the CHD population. 46 , 49–53 We had initially considered several questionnaires for the QUALIREHAB trial, as other HRQoL instruments with good psychometric properties have been used in the paediatric and adult CHD populations.…”
Section: Methodssupporting
confidence: 69%
“…Psychometric properties showed reliability, validity, and responsiveness to clinical change over time, including the French version of the PedsQL. 45 , 46 In previous studies using various HRQoL instruments, 37 , 43 , 47 , 48 our group also found a good sensitivity of the PedsQL generic questionnaire in the CHD population. 46 , 49–53 We had initially considered several questionnaires for the QUALIREHAB trial, as other HRQoL instruments with good psychometric properties have been used in the paediatric and adult CHD populations.…”
Section: Methodssupporting
confidence: 69%
“…These QoL levels may reflect the medical advances in screening and care for CHD in recent decades [ 40 , 41 ]. Indeed, to date, over 90% of children with a CHD are expected to survive more than 30 years after the first cardiac surgery [ 3 , 10 , 40 42 ]. In addition to this, our patients and their parents are involved in a multidisciplinary standardized follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the prevalence of CHD is around 7 per 1000 births [ 2 ]. In the past two decades great medical and surgical advances have significantly increased life expectancy [ 3 , 4 ] and the probability of survival beyond the first year of life has increased to 90% among individuals born with CHD [ 5 , 6 ]. Thus, most children and adolescents with CHD are expected to reach adulthood [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de que no existen estudios prospectivos de alta calidad que orienten la decisión sobre la participación en deportes en este tipo de pacientes (17), las recomendaciones actuales demuestran que, si en estos pacientes se realiza una correcta evaluación inicial, una estratificación de riesgo adecuada y un tratamiento ajustado a la condición, se puede lograr un retorno deportivo seguro de pacientes con SQTL1 (18). En este sentido, la toma de decisiones compartida entre el paciente, su familia, y el médico tratante, junto con ciertas recomendaciones generales, como son la evaluación clínica exhaustiva con un especialista en arritmias, evitar la participación en deportes competitivos en pacientes sintomáticos hasta notificar a los familiares, definir un plan de manejo y permanecer asintomáticos durante al menos 3 meses después del inicio de la terapia, tomar medidas de prevención como evitar el uso de medicamentos que prolonguen el QT, mantener una correcta hidratación y reposición de electrolitos, gestionar la hipertermia y contar con un desfibrilador externo automático personal, además de considerar un plan de acción frente a emergencias, podrían ser factores cruciales al tomar una decisión con respecto al retorno al deporte con un bajo riesgo de complicaciones (17)(18)(19).…”
Section: Reportes De Casounclassified